Kontradiksi Mentoring Poligami Coach Hafidin dengan Asas Monogami Perkawinan - Khusnul Amalia (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research discusses the contradictory aspects of Coach Hafidin's polygamy mentoring with the principle of monogamous marriage in the context of Indonesian family law. The aim of the article is to analyze and scrutinize Coach Hafidin's controversial statements and Coach Hafidin's polygamy, exploring their impact on societal perceptions of polygamy. The research adopts a qualitative analysis of Coach Hafidin's statements and actions, highlighting the contradictions with monogamous principles and their implications for public opinion. The findings reveal a significant discord between mentoring practices and established principles, raising concerns about the potential influence on the institution of marriage in Indonesia. This study contributes to the discipline by shedding light on the tensions between polygamy mentoring and the prevailing principles of monogamy, offering insights into the evolving landscape of family values in Indonesian society.